O języku dekadentów. Wokół wypowiedzi Józefa Weyssenhoffa z 1891 roku - Ataman, Klaudia (Poznańskie Studia Polonistyczne. Seria Literacka, 2024)
The aim of this article is to present the decadent style, a phenomenon overlooked by contemporary research on early modernism, based on the statements of Józef Weyssenhoff (“New literary phenomenon. Maurycy Maeterlinck and symbolic decadentism”, Biblioteka Warszawska 1891, vol. 2). The discussion of Weyssenhoff's text leads to the conclusion that the authors of discussions, reviews and summaries of French literature from the turn of the 1890s saw its uniqueness primarily in the linguistic layer, treating the worldview aspect as definitely secondary.